2016
DOI: 10.1155/2016/2063985
|View full text |Cite
|
Sign up to set email alerts
|

CXCL13 Promotes Proliferation of Mesangial Cells by Combination with CXCR5 in SLE

Abstract: As a CXC subtype member of the chemokine superfamily, CXCL13 is considered to be involved in systemic lupus erythematosus (SLE), especially in lupus nephritis (LN). To determine the effect of CXCL13 on SLE and explore the potential mechanisms, we tested serum concentrations of CXCL13 in patients and healthy individuals and found that CXCL13 expression was high in SLE patients especially in LN patients. When we treated human renal mesangial cells (HRMCs) in vitro with recombinant human CXCL13, the cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…B cell gene signatures CD19, TNFRSF17 , and MS4A1 were significantly enriched in CLE skin tissue compared to healthy controls. High expression of NK cell signatures ( IL21R, KLRB1, KLRD1 , and KLRK1 ) and Cytotoxic T cell signatures ( CTSW, CD8A, EOMES , and LAG3 ), as well as associated GZMB and GZMA , support previous CLE studies that described cytotoxic signatures ( 48 51 ). There was no difference in the expression of IL4 , a Th2 cell gene signature, even though some studies have proposed the role of Th2 cells in the pathogenesis of CLE ( 52 ).…”
Section: Discussionsupporting
confidence: 83%
“…B cell gene signatures CD19, TNFRSF17 , and MS4A1 were significantly enriched in CLE skin tissue compared to healthy controls. High expression of NK cell signatures ( IL21R, KLRB1, KLRD1 , and KLRK1 ) and Cytotoxic T cell signatures ( CTSW, CD8A, EOMES , and LAG3 ), as well as associated GZMB and GZMA , support previous CLE studies that described cytotoxic signatures ( 48 51 ). There was no difference in the expression of IL4 , a Th2 cell gene signature, even though some studies have proposed the role of Th2 cells in the pathogenesis of CLE ( 52 ).…”
Section: Discussionsupporting
confidence: 83%
“…Other studies have also observed the association between CXCL13 level and disease activity in SLE, for example, with lupus nephritis (LN). 31,32 Schiffer et al demonstrated that serum levels of CXCL13 in SLE patients were higher than those observed in healthy controls. In patients with LN, the level of this chemokine was even higher compared to those without LN.…”
Section: Discussionmentioning
confidence: 99%
“…In the last couple of decades, increasing evidence has linked CXCL13/CXCR5 axis to SLE and its major manifestations. Serum CXCL13 levels are found to be significantly higher in SLE patients, especially in those with renal involvement, as compared with healthy controls (83,84). Serum CXCL13 is positively correlated with the SLE Disease Activity Index (SLEDAI) (84,144,145), anti-double-stranded DNA (anti-dsDNA) antibodies titers, and prevalence of inflammatory arthritis, while it is inversely correlated with serum levels of complement factors C3 and C4 (146)(147)(148).…”
Section: Cxcl13/cxcr5 Axis In Systemic Lupus Erythematosusmentioning
confidence: 97%
“…Serum CXCL13 levels are found to be significantly higher in SLE patients, especially in those with renal involvement, as compared with healthy controls (83,84). Serum CXCL13 is positively correlated with the SLE Disease Activity Index (SLEDAI) (84,144,145), anti-double-stranded DNA (anti-dsDNA) antibodies titers, and prevalence of inflammatory arthritis, while it is inversely correlated with serum levels of complement factors C3 and C4 (146)(147)(148). CXCL13 is also a potential differentiation marker to identify active SLE from inactive SLE, and to identify LN from non-LN in SLE patients (148).…”
Section: Cxcl13/cxcr5 Axis In Systemic Lupus Erythematosusmentioning
confidence: 99%